Studi Cross Sectional Terhadap Faktor Risiko Hipertensi pada Remaja - Rezekiyah, Sholeha; Wahyuni, Evi; Karwiti, Witi; Nasrazuhdy, Nasrazuhdy; Lestari, Wuni Sri (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to look at the risk factors for hypertension in adolescents. The method is observational analytical research using a cross-sectional design involving 63 respondents. The research results showed that the 63 teenagers willing to be respondents in this study were aged 14 - 18 years, with the majority being female. The research results showed that the gender variable was not related to the incidence of hypertension in adolescents (p = 0.245), as well as the sleep duration variable (p = 0.477), the BMI variable (p = 0.000), light exposure (p = 0.000) and total cholesterol levels. (p = 0.007) shows a relationship with the incidence of hypertension in adolescents. The research conclusion is that the incidence of hypertension in adolescents is related to BMI, light exposure, and total cholesterol levels. Keywords: Risk Factors, Hypertension, Adolescents